DESIGN, MANUFACTURING, AND VIBRATION MEASUREMENTS OF PROXIMITY SENSOR ADAPTER - FAQIH ALDIAS (NIM : 131 05 078); Pembimbing, Dr. Ir. Zainal Abidin, MOHAMAD
In many industries, one of parameters that is measured for predictive maintenance purpose is shaft vibration. Shaft vibration is measured by proximity sensors which are installed perpendicular one to each the other inside a bearing housing. However, the use of proximity sensors inside the bearing housing to measure shaft vibration has several limitations, such as difficult to replace when the sensor is damaged, and the measurement results are influenced by non-homogeneity of the electric properties of shaft materials. To provide solutions for shaft vibration measurement problems, the objective of the final project is to design and manufacture proximity sensor adapter. The adapter is designed to have a mechanism which allows easy sensor maintenance, and also minimizes the effect of electrical non-homogeneity of the shaft. There are two prototypes designed and tested in this research. The 2nd prototype is the improvement of the 1st prototype. The evaluation results of the design of the 1st prototype are used as inputs in the design of the 2nd prototype adapter. FRF measurement results show that the value of natural frequency of the 2nd prototype is higher than that of the 1st prototype. Calibration test result shows that the operating frequency of the 2nd prototype is also wider than that of 1st prototipe. Another result shows that the shaft vibration measurement by proximity sensor adapters are not affected by electrical non-homogeneity of the shaft. Based on these vibration testing results, the design and performance of the 2nd prototype proximity sensor adapter is better than that of the 1st prototype.